Smoking cessation reduces ratio of total cholesterol/high density lipoprotein (HDL) cholesterol levels on adult people in Yogyakarta Special Region - Arta Farmawati; Ratika Marchelaona; Dina Septari Anindyah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Cigarette smoking is a major cause of cardiovascular disease due to elevation of free radical substances as well impairment in lipid metabolism. Smoking cesation has been linked with reduced risk of mortality. However, data regarding cardiovascular disease (CVD) risk factor in former smoker is limited. The aim of the study was to evaluate the CVD risk factor among smoker, non-smoker and former smoker in Yogyakarta Special Region, Indonesia. A cross-sectional design from 86 apparently healthy male, aged between 25-50 years old was performed for this study. From total subjects, 45 subjectsare smokers, 26 are non-smokers and 15 are former smokers. Body weight, height, and blood pressure were also measured from the subjects. Blood was drawn for assessment of total cholesterol (TC), triglyceride, low density lipoprotein (LDL), high density lipoprotein(HDL) and C-reactive protein (CRP) concentrations. We found significant difference in the level of HDL, cardiovascular risk index (LDL/HDL ratio), atherogenic index (TC/HDL ratio) and also in systolic blood pressure among groups (p<0.05). Smoking person hadsignificantly low HDL level with high CVD risk index and atherogenic index (p<0.05). The CVD risk index was not different between former smoker and smoker groups. Serum CRP level was not different among the groups. In conclusion, smoking is associated with increased risk of CVD. Smoking cessation slightly decrease the CVD risk.